Polymers from Fossil and Renewable Resources Scientific and Technological Comparison of Plastic Properties - Ciardelli, Francesco; Bertoldo, Monica; Bronco, Simona; Passaglia, Elisa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book describes the development and commercialization of materials with viscoelastic properties, placing particular emphasis on the scientific and technological differences between plastics and bioplastics. The authors explain how to handle each of the two types of materials and determine the comparative environmental impact of the material life-cycle. The practical values of the overlapping aspects of the two types of materials from technical properties to eco-compatibility are also discussed.
Basic Concepts for Plastic Response -- Material Plasticity -- Measurable Fundamental Entities -- Processing Features -- Molecular Structure Requirements -- Oil Derived Macromolecules -- Renewable Macromolecules -- Structure/ to Fundamental Properties -- Preparation of Macromolecules for Plastics -- From Oil to Macromolecules -- Polymerization Processes -- Processing to Materials -- The Obtainment of Bioplastics -- Biopolymers from Natural Sources -- Monomers from Nature -- Products Preparation -- Hybrid Materials and Systems -- Chemical Modification of Molecular Structure -- Blends and Composites -- Functional Materials -- Environmental Impact -- Materials from Oil and Nature -- Production Processes -- Consumer Use -- Disposal, Recycling, Biodegradation -- Response of Society and Market -- Availability of starting materials -- Ultimate Properties for Application -- Evaluation and Future.
Keywords: Biomaterials; Polymers; Renewable energy sources; Biomaterials; Polymers; Renewable Energy